Dosimetry induced modifications in structural, magnetic and Mössbauer spectroscopy studies of 60Co γ-irradiated Co0.5Ni0.5Fe2O4. (December 2021) - Srinivasamurthy, K.M.; Manjunatha, K.; El-Denglawey, A.; Kubrin, S.P.; Sarychev, D.A.; Mašláň, M.; Pattar, Vinayak; Angadi V, Jagadeesha
Abstract: In the present work, we report structure, magnetic and Mössbauer spectroscopic studies of nanocrystalline Co0.5 Ni0.5 Fe2 O4 ferrites irradiated with different doses (0, 50 and 100 kGy) of 60 Co γ-irradiation. Samples are synthesized by solution combustion route. γ-Irradiation of all nanoparticles preserves the stable spinel cubic (Fd-3m) structure, as confirmed by X-ray diffractogram. XRD analysis reveals that the lattice parameter found in the range of 8.339–8.361 Å. The lattice parameter increased after gamma irradiation. FTIR spectra shows two absorption bands, which confirms the formation of spinel cubic structure. The magnetic behavior of the samples was further investigated using a Vibrating sample magnetometer and Mössbauer spectroscopy. The saturation magnetization found in the range of 55.39–47.81 emu/g. The saturation magnetization and remnant magnetizations of the pristine samples persist even after irradiation also. The magnetic coercivity found in the range of 931–892 Oe. The coercivity decreases with irradiation, indicating a reduction of magnetic anisotropy in the nanoparticles. After γ-irradiation, the redistribution of cations among the A-site and B-site with dose the magnetic coercivity in the samples brings down in the nanoparticles. At low temperature (14 K) and room temperature, Mössbauer spectroscopy has been done to thorough the hyperfine structure of unirradiated and irradiated nanoparticles. The spectral parameters related to the occupation of Fe 3+ ions at the A-site and B-site. The variation in magnetic properties is due to the cation redistribution among A and B interstices. These emerge are cautious to comprehend the nature and stability of the magnetic strength of Co0.5 Ni0.5 ferrite nanoparticles. Highlights: Gamma-irradiated effect on Co0.5 Ni0.5 Fe2 O4 reported for the first time. Stable spinel cubic structures were confirmed by after irradiation. Coercivity decreases with different dose rate of irradiation. Mossbauer spectroscopy has been done irradiated nanoparticles samples.